2012
DOI: 10.1016/j.socscimed.2012.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood poverty, park use, and park-based physical activity in a Southern California city

Abstract: A rich literature indicates that individuals of lower socio-economic status engage in less leisure time physical activity than individuals of higher socio-economic status. However, the source of the difference is believed to be, in part, due to differential access to resources that support physical activity. However, it has not been shown as to whether equal access to parks can mitigate differences in leisure time physical activity. Using systematic direct observation, we quantified physical activity in neighb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
112
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 114 publications
(125 citation statements)
references
References 40 publications
8
112
1
4
Order By: Relevance
“…The Los Angeles park study produced similar findings, with parks found to be used less by residents in low-income areas than in medium-and high-income areas, even after accounting for differences in park size, staffing, and programming (Cohen, Han, Derose, Williamson, Marsh, Rudick, et al, 2012).…”
Section: Socioeconomic Statusmentioning
confidence: 63%
“…The Los Angeles park study produced similar findings, with parks found to be used less by residents in low-income areas than in medium-and high-income areas, even after accounting for differences in park size, staffing, and programming (Cohen, Han, Derose, Williamson, Marsh, Rudick, et al, 2012).…”
Section: Socioeconomic Statusmentioning
confidence: 63%
“…However, these parks do have fewer facilities and lack programming, which is known to attract park users. 8,16 Because it appears that a considerable percentage of the population in these neighborhoods suffer from disabilities, it would be important to consider installing special facilities like universally accessible inter-generational playgrounds. Programming should be provided and tailored for local needs, such as low-impact aerobic exercises and other classes for the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…6 Similarly, although most urban residents live within one half mile of a public park 7 , parks are often underutilized. [8][9][10] Inner cities often have multiple parks and plazas in close proximity to people's homes, yet the presence of facilities alone may be insufficient to encourage people to spend time outdoors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If and how resources are used may partly depend on sense of coherence: while a stronger sense of coherence might allow for health-promoting use of resources even in a resource-poor environment, easily identifiable and useable resources might be crucial for engagement in health-promoting behaviour for people with a weaker sense of coherence. Merely placing resources into a context might primarily benefit people with a strong sense of coherence, and thereby could even widen the gap in health (Cohen et al, 2012).…”
Section: Salutogenesis and The Urban Environmentmentioning
confidence: 99%